Seniman Dalam Perputaran Pasar Seni Rupa - Wulandari, Retno (Institut Seni Indoensia Surakarta, 2012)
After the booming, Indonesian art of painting come in to the era of the rise and the fall of the art of painting that happen very fast and drastic. Artists are often suddenly shocked and not ready to face a long famine era, because they are not ready and do not supply themselves with knowledge of their own art creating technique and infrastructure that built Indonesian art of painting market. It is only fitting that artists realize and ready to get in to the system that create art of painting market, because they have to behave as stakeholder for their own works, whether they want to or not. The principles â€œArt for Artâ€ and â€œArt for Marketâ€ have to pass and to do in harmony without forcing to sacrifice the idealism in art work creating. Cooperation in all line, including artists, curators, art galleries, collectors, market and press, have to be ran in balance. Although it can not be denied that there are still many artists are â€œlazyâ€ to get in and collaborate with one of those stakeholders. But, when artists start to have contact with market, the collaboration have to do for good cooperation and communication, because, however, market is one of the things that will establish Indonesian art of painting in the future, with focus on works quality and how the artist will survive in the world of art working.Keywords:Â artist, gallery, collector, market